Allogeneic and syngeneic hematopoietic cell transplantation in patients with amyloid light-chain amyloidosis: a report from the European Group for Blood and Marrow Transplantation - Schönland, Stefan; Lokhorst, Henk; Buzyn, Agnes; Leblond, Veronique; Hegenbart, Ute; Bandini, Giuseppe; Campbell, Andrew; Carreras, Enric; Ferrant, Augustin; Grommisch, Leanthe; Jacobs, Peter; Kröger, Nicolaus; et al. (Blood, 2006)
Using the European Group for Blood and Marrow Transplantation (EBMT) registry, we retrospectively studied 19 patients with AL (amyloid light-chain) amyloidosis who underwent allogeneic (allo; n = 15) or syngeneic (syn; n = 4) hematopoietic stem cell transplantation (SCT) between 1991 and 2003. For allo-SCT, full-intensity conditioning was used in 7 patients and reduced-intensity conditioning (RIC) in 8 patients. Engraftment was durable in 12 of those 15 patients. The median follow-up time is 19 months. Kaplan-Meier probabilities of overall and progression-free survival were 60% and 53% at 1 year, respectively. Overall, 40% of patients died of transplant-related mortality (TRM). Best hematologic response after SCT was complete remission (CR) and partial remission (PR) in 8 and 2 patients, respectively, leading to an organ response in 8 of these patients. Seven of the 10 patients in remission are long-term survivors. In 5 of 7 evaluable patients in CR, chronic graft-versus-host disease (GvHD) was observed, indicating the contribution of immune effects to disease control. The main clinical problem was cardiac failure in patients with poor performance status due to amyloidosis or in combination with severe infections. These data suggest that allo-SCT might be a promising and potentially curative treatment modality for selected patients with AL amyloidosis. (Blood. 2005;107:2578-2584)